2019
DOI: 10.1111/and.13496
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term NaHS administration reduces oxidative stress and apoptosis in a rat model of left‐side varicocele

Abstract: The main aim of this study was to assay the testicular H2S levels in the varicocele rat model and then to investigate the protective effects of NaHS on morphometric changes, sperm parameters, oxidative stress and apoptosis markers in rat's testis. D,L‐propargylglycine (PAG) was administrated to show the effects of cystathionine γ‐lyase enzyme (CSE) inhibition in the varicocele. Rats were assigned to four groups: (a) Sham, (b) varicocele, (c) varicocele + PAG and (d) varicocele + NaHS. Animals in varicocele + N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Please note that groups with common 'a' are also significantly different from each other only for sperm motility and not for sperm abnormal morphology Micheli et al, 2019) which includes reduced tubule differentiation index, spermiation index, the diameter of seminiferous tubes, Johnson score as well as sperm parameters and sperm functional tests. These results are in keeping with our previous studies and several other studies have explained that due to the increased testicular heat stress in varicocele conditions and subsequent increased oxidative stress, abnormal sperm chromatin packaging and DNA fragmentation are among the common pathological feature of varicocele (Asadi et al, 2018;Lorian et al, 2020;Razi et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Please note that groups with common 'a' are also significantly different from each other only for sperm motility and not for sperm abnormal morphology Micheli et al, 2019) which includes reduced tubule differentiation index, spermiation index, the diameter of seminiferous tubes, Johnson score as well as sperm parameters and sperm functional tests. These results are in keeping with our previous studies and several other studies have explained that due to the increased testicular heat stress in varicocele conditions and subsequent increased oxidative stress, abnormal sperm chromatin packaging and DNA fragmentation are among the common pathological feature of varicocele (Asadi et al, 2018;Lorian et al, 2020;Razi et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, NaHS administration did not change body weight; this finding is in line with other studies in male mice 22 , 23 and male rats 18 ; however, two studies reported that NaSH restored reduced body weight in nephrectomized rats 24 , 26 and other studies did not report an effect of NaSH administration on body weight 15 17 , 19 21 , 25 . In addition, in our study, NaSH administration did not affect serum urea and Cr, a finding that aligns with another report 25 .…”
Section: Discussionsupporting
confidence: 92%
“…Despite evidence that NaHS solutions are not stable, some animal studies used NaHS solutions in drinking water as an H 2 S-donating compound 15 26 , with the duration of intervention ranging from 1 to 21 weeks (Table 2 ). These studies refreshed NaHS solutions every 12 15 , 17 , 18 , 24 , 25 or 24 19 23 h. Our results indicate that due to H 2 S loss from the NaHS solution, rats are not exposed to a stable concentration of the drug, and a large fluctuation in the content of NaHS in the drinking water of rats occurs over 12 or 24 h (see Fig. 2 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The interventional or surgical approach is considered the standard of care for the condition in case of infertility due to favourable outcomes regarding improvement in semen parameters and pregnancy rates (2). In modern era, research has also focused on the varicocele-induced oxidative stress and reduction in antioxidant capacity which results in impaired spermatogenesis, broadening new horizons in the treatment of the condition (3,4). Antioxidative treatment is well-established in idiopathic infertility and oligoasthenoteratospermia (OAT), albeit the results still conflicting and the optimal agents or combination still lacking (5).…”
Section: Introduction -Backgroundmentioning
confidence: 99%